Impact of seasonal variations on polyphenolic content and antibacterial activity in Berberis lycium Royl - Bibi ZAINAB; Zainab BIBI; Khanum KHOLA; Lin ZHOU; Zafar MAHNOOR; Mehmood Abbasi ARSHAD (KeAi Communications Co., Ltd., 2023)
Periodic changes in the environmental conditions affect significantly on the biosynthesis of bioactive compounds and the therapeutic potential in medicinal plants. Although Berberis lycium is being extensively used against various ailments, specifically infectious diseases, impact of seasonal variations on its polyphenolic contents and antibacterial activities has rarely been explored yet. Consequently, present study was focused on the determination of phenolics and flavonoids content and antibacterial activities in the root and stem bark of B. lycium harvested throughout the year from same location (Abbottabad) using standard analytical approaches. Relatively, stem bark had high concentration of total phenolics than root bark, but in the case of total flavonoids there was no significant difference. In root bark, the highest concentration of TPC was in the month of December (373.5±0.58 mg GAE/100 g DW), while stem bark exhibited highest concentration of TPC (476.1±13.7 mg GAE/100 g DW) in the month of January. In root bark, TFC ranged from 32.00±7.62 to 124.5±5.58 mg QE/100 g DW with highest concentration in April. Whereas, in stem bark, TFC varied from 19.51±4.94 to 135.50±7.11 mg QE/100 g DW, with highest concentration in the month of April. Likewise, in January, November and December inhibition potential was maximum against Escherichia coli and Staphylococcus aureus both in root and stem bark samples. Although, significant associations were observed between total phenolics and antibacterial activities. However total phenolics, total flavonoids, and antibacterial activities depicted negative correlations with growing conditions viz. temperature, rain fall and humidity. Our findings confirm the impact of seasonal variations on the phytochemical composition and bioactive potential in medicinal plants. Specifically, to get maximum health benefits from B. lycium, winter season could be more appropriate in the Himalayan region.